Um formalismo relacional para o desenvolvimento de arranjo físico industrial. - Torres, Isaías (2007)
The facility layout planning is an important factor of production systems. It is an important step of the facility planning process where converge determinants from business strategy, economic and work factors, among others. The knowledge and techniques of this application area have evolved as the factory concept itself have changed and new aspects were considered as important ones. The traditional tools and techniques have considered just part of the aspects related to the layout, as proximity relationships and material flows. This work aimed to determine a formalism able to represent, in an integrated way, the aspects considered during the creation and evaluation of layout alternatives by multidisciplinary design teams. This formalism, based on objects and relationships, breaks with the prescriptive vision present in traditional facility layout software. The software that has been developed from the formalism presents an innovative way for layout designing, and points out to several other innovation opportunities. It is expected that this formalism may be used for developing software to support work activities of people involved with industrial facilities planning.